(untitled) (Ustozlar uchun, 2026)
The preservation and study of dialects play an important role in modern linguistics and translation studies. Southern Uzbek dialects constitute a significant part of the linguistic and cultural heritage of the Uzbek people. These dialects possess distinctive phonetic, lexical, morphological, and syntactic characteristics that differentiate them from Standard Uzbek and contribute to the richness of the national language. The relevance of the research is determined by the growing interest in the interaction between language, culture, and translation. Dialectal units often contain cultural information, local traditions, and social values that cannot always be conveyed directly in another language. Therefore, the translation of dialectal elements remains one of the most challenging issues in literary translation.